PENGARUH LOKASI, PERSEPSI HARGA DAN KELENGKAPAN PRODUK TERHADAP LOYALITAS PELANGGAN PADA CS MINIMARKET PAUH KAMBAR NAN SABARIS - Yanti, Novi (Menara Ilmu, 2017)
This study aims to determine the influence of location, price perceptions and completeness of the product to customer loyalty on CS minimarket Pauh Kambar Nan Sabaris. This study is a survey study obtained based on the questionnaire distribution. The population in this research is minimarket customer of Pauh Kambar Nan Sabaris. The sample used in this study were 70 respondents, using sampling technique accidental sampling, the data was processed with SPSS 16.0. The results can be concluded; 1) Location affects customer loyalty on CS minimarket Pauh Kambar Nan Sabaris sig 0,012<(0,05); 2) Price perceptions affect customer loyalty at CS minimarket Pauh Kambar Nan Sabaris sig0,003<(0,05);3) Product completeness affects customer loyalty at CS minimarket Pauh Kambar Nan Sabaris sig 0,017<(0,05) and 4) Location, price perception and completeness of product together influence to customer loyalty at CS minimarket Pauh Kambar Nan Sabaris sig 0,000<(0,05) with regression coefficient Y = 0,952 + 0,204X1 + 0.314X2 + 0.204X3 with R = 0.577 or R2 = 0.333. Location, perception of price and completeness of the product affects customer loyalty of 33.3%, while the remaining 66.7% influenced by other variables outside of this research variables. Keyword : Location, Price Perception, Product Completeness, Customer Loyalty.